Analisis Persepsi Pedagang Pasar Rakyat tentang Bank Syariah (Studi Kasus Kecamatan Pariaman Tengah) - Yovi Savitri; Ali Rahman (ARZUSIN, 2026)
Although traders’ perceptions of Islamic banks have received attention in various studies, research specifically analyzing traditional market traders’ perceptions based on their experiences, knowledge, and transaction needs remains relatively limited. This study aimed to analyze the perceptions of traders at the Pariaman Tengah Subdistrict Traditional Market toward Islamic banks and identify the factors influencing the formation of these perceptions. The study employed a qualitative approach with a descriptive field research design. The study involved nine informants, consisting of eight traders as primary informants and one market head as a supporting informant, who were selected through purposive sampling. Data were collected through observation, semistructured interviews, and documentation and were subsequently analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which comprises data condensation, data display, and conclusion drawing and verification. The results showed that traders’ perceptions of Islamic banks remained varied. Some traders had positive perceptions because they understood Islamic principles, whereas most traders continued to use conventional banks because of considerations related to ease of access, the availability of facilities, and business transaction needs. The levels of knowledge, experience, trust, and exposure to information about Islamic banking were the primary factors shaping traders’ perceptions. These findings reinforce perception theory, which explains that knowledge and experience play a role in shaping individuals’ perceptions of an object. This study contributes to the development of the literature on public perceptions of Islamic banking and provides practical implications for Islamic banks and the government in improving Islamic financial literacy, outreach, and financial inclusion among traditional market traders.